2016
DOI: 10.17988/bedi-41-04-196-208.1
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Paradigms to Better Serve Twice-Exceptional African-American Learners

Abstract: Existing research on students with twice-exceptional abilities concentrates on strategies to improve the educational experiences of individuals who demonstrate the comorbid presence of a talent for high academic achievement (often considered a strength) and a disability (often considered a weakness). However, this body of work typically excludes the sociocultural context in which these abilities manifest and how the current deficit perspective of ability infringes upon an appropriate education for African-Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
(83 reference statements)
0
8
0
1
Order By: Relevance
“…With these challenges of developing healthy racial, gender, and academic identities, it is easy to see how the development of CCR can be difficult. Gifted Black males with disabilities are likely to have negative experiences in schools with both peers and educators and have limited access to courses and other opportunities that are appropriately challenging (Owens, Ford, Lisbon, & Owens, 2016;Robinson et al, 2014;Trotman Scott et al, 2015). Current literature suggests that Black males may engage individually with school counselors concerning math and science courses as well as college going when they had a greater sense of school belonging (Qi & Goings, 2018).…”
Section: Giftedness and Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…With these challenges of developing healthy racial, gender, and academic identities, it is easy to see how the development of CCR can be difficult. Gifted Black males with disabilities are likely to have negative experiences in schools with both peers and educators and have limited access to courses and other opportunities that are appropriately challenging (Owens, Ford, Lisbon, & Owens, 2016;Robinson et al, 2014;Trotman Scott et al, 2015). Current literature suggests that Black males may engage individually with school counselors concerning math and science courses as well as college going when they had a greater sense of school belonging (Qi & Goings, 2018).…”
Section: Giftedness and Disabilitymentioning
confidence: 99%
“…Despite challenges of being properly identified and served in either setting, gifted Black males with disabilities can be successful. This is particularly true when Black males are able to achieve strong identities (Mayes & Moore, 2016a, 2016bOwens et al, 2016) and receive the appropriate supports needed to reach their potential. For example, strong cultural identities can allow for Black boys to harness the strength necessary to navigate the negative messages and experiences they may face regarding their masculinity, giftedness, and disability.…”
Section: Giftedness and Disabilitymentioning
confidence: 99%
“…In the literature on twice-exceptional learners, there are few investigations of parenting experiences (Besnoy et al, 2015; Neumeister, Yssel, & Burney, 2013; Rubenstein, Schelling, Wilczynski, & Hooks, 2015) and only one focusing on a racial/cultural diverse population (Owens, Ford, Lisbon, & Owens, 2016). Besnoy et al (2015) found that parents reported few available educational resources, and acquisition of professional knowledge about diagnosis, educational policies, and law are deemed critical prerequisites for advocacy.…”
Section: Parents Of Children With Exceptionalitiesmentioning
confidence: 99%
“…Neumeister et al (2013) also emphasized the importance of parents’ advocacy by examining successful twice-exceptional children and their parents’ efforts in seeking out resources. Owens et al’s (2016) case study analysis of a high-ability African American student with an emotional and behavioral disorder described parental discipline techniques used to address the child’s violent behaviors and his improvement, but detailed parenting practices and experiences were minimally discussed. In sum, parents of twice-exceptional children often find it difficult to discover appropriate educational services, despite their extensive advocacy efforts, and less is known about the experiences of culturally diverse parents with twice-exceptional children.…”
Section: Parents Of Children With Exceptionalitiesmentioning
confidence: 99%
“…A reader's identity becomes shaped by the intersection of factors that are both inherent and neurologically based, and factors that arise as a result of one's home and academic environment (Anderson & Sadler, 2009;Hoyles & Hoyles, 2010;Mayes, Hines, & Harris, 2014). This article will consider the inherent factors of race for African American boys building a reader's identity in the PreK-12 setting as well as factors specific for the 2e learner (Owens, Ford, Lisbon, & Owens, 2016).…”
Section: Introductionmentioning
confidence: 99%